Molecular and Microbiological Evaluation of Carbapenem-Resistant Enterobacteriaceae (CRE) at Two Centers in Texas. (4th October 2017) - Serrano, Ruth; Matheu, Michelle; Perez, Federico; Patterson, Jan E; Dallas, Steven; Rudin, Susan D; Bonomo, Robert A; Traugott, Kristi; Cadena, Jose
Abstract: Background: CRE cause substantial morbidity and mortality. The purpose of this study was to describe the clinical, epidemiological, molecular and microbiologic characteristics of our patients with CRE. Methods: Patients with CRE strains isolated from July 2013 to July 2015 were identified at a tertiary care VA hospital and a university-affiliated hospital in San Antonio. CRE was defined as a strain with imipenem, meropenem, or doripenem MIC ≥2 μg/ml or disk diffusion zone diameter ≤22 mm (using 10 μg disks) and resistance to ceftriaxone, cefotaxime, or ceftazidime. Molecular characterization was performed for detection of β-lactamase genes in 19 isolates. Results: A total of 25 patients were identified. Thirteen had CRE infections; the remaining were colonized. Seventeen (68%) were men and average age was 55 years. Nineteen (76%) patients were hospitalized and 57.8 % of them were readmitted within 30 days. Thirty day mortality was 20%. Sixty percent had history of multi-drug-resistant organisms. Patients had history of prior hospitalization (88%), surgery (76%) and central line (72%). Only 12% received appropriate empiric therapy. Klebsiella pneumoniae was the most common isolate (60%) followed by Escherichia coli (28%) and Enterobacter (12%). Ceftazidime–Avivactam (CAZ-AVI) susceptibility was tested in 18 isolates and they were all found to be susceptible by FDA approved breakpoints. K. pneumoniae carbapenemases ( bla KPC ) were identified in 10 isolates (52.6%). No oxacillinase-48-type carbapenemases (blaOXA48 ) or New Delhi metallo-β-lactamase ( bla NDM ) were detected. Prior healthcare exposures are listed in Table 1. Conclusion: CRE continues to be infrequent at South Texas but it is associated with high morbidity and mortality. Patients with CRE had frequent healthcare contact, especially acute long-term facilities, and bla KPC was the most common carbapenemase detected. All isolates were susceptible to CAZ-AVI. Disclosures: All authors: No reported disclosures.